Bioethics and the Patent Eligibility of Human Embryonic Stem Cells-Related Inventions in Europe - Ugurlu, Ali Seyhan (Munich Intellectual Property Law Center - MIPLC, 2014)
The topic of this book is one of the most contentious, complex and at the same time very important in many respects. Latest achievements in the biotechnology industry related to the stem cell technology are quite important.